ORIGINAL COST AS A RATE BASE. - Bonbright, James C. (The Accounting Review, 1945)
The fallacy of the argument in favor of a rate base measured not by original cost but by subsequent purchase price should be apparent to anyone who understands the basic philosophy of the "prudent investment" standard. Under this standard, consumers of public utility service compensate investors for building the plants, not just for buying them from other persons who have already built them and who have already devoted them to the public service. Once these utility properties have been built and have been put into public service, investors who buy them later from their original owners are simply taking over these former owners' claims to a return on the capital devoted to the public service. The very nature of rate regulation precludes the adoption of the transfer price of a utility property, presented under the guise of actual cost to the present accounting company, as a proper measure of the rate base. This is so because public utility properties are necessarily bought and sold at prices reflecting the expectations of the buyers and sellers as to what the properties can be made to earn in the future.